2012
DOI: 10.1002/jaal.00074
|View full text |Cite
|
Sign up to set email alerts
|

A Different Kind of Reading Instruction: Using Visualizing to Bridge Reading Comprehension and Critical Literacy

Abstract: Many literacy teachers are creating contexts for students to learn and use a range of reading comprehension strategies. As useful as reading strategy instruction is, relatively little has been documented on the ways in which reading strategies can become tools for critical literacy. In this paper, the author illustrates how a reading strategy can become a tool for critical literacy, focusing on the specific strategy of visualizing. Drawing on data collected from a yearlong qualitative study of three after‐scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
1
22
0
5
Order By: Relevance
“…It can motivate students to read books and begin discussions on difficult issues of power, race, gender, and class (McLaughlin & Allen, 2002). In line with this, Park (2012), also Peterson and Chamberlain (2015) found that the implementation of critical literacy could support students to become aware to other people, society, power, culture, and especially the text itself.…”
Section: B the Importance Of Critical Literacymentioning
confidence: 64%
“…It can motivate students to read books and begin discussions on difficult issues of power, race, gender, and class (McLaughlin & Allen, 2002). In line with this, Park (2012), also Peterson and Chamberlain (2015) found that the implementation of critical literacy could support students to become aware to other people, society, power, culture, and especially the text itself.…”
Section: B the Importance Of Critical Literacymentioning
confidence: 64%
“…It suggested that when a user can visualise a text, he/she is reading, he/she is also able to get the meaning conveyed by the text. Put simply; visualisation strategy fosters critical literacy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also indicated the advantage of the approach in reading [5]- [7]. Most of these past and current researchers introduced visualisation to read non-academic texts.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, academic words are more 14 abstract than general high frequency words (e.g., metacognition, paradigm). Further evidence to these claims comes from previous research that has pointed to EAP learners' difficulties with EAP reading (Clark & Ishida, 2005;Park, 2012;Vongpumivitch, Huang, & Chang, 2008) and…”
Section: Academic Vocabularymentioning
confidence: 97%
“…Further research conducted on the usefulness of academic words confirms these arguments, indicating the supportive role of academic words in English academic texts (Campion & Elly, 1971;Cowan, 1974;Durrant, 2016;Farrell, 1990;Hutchinson & Waters, 1987;Nagy & Townsend, 2012;Nassaji, 2006;Praninskas, 1972;Staehr-Jensen, 2005;Trimble, 1985). For example, it has been found that academic vocabulary plays a role in L2 learners' academic achievements (Garcia, 1991;Li & Pemberton, 1994;Qian 1999Qian , 2002Snow, 2010;Stahl & Fairbanks, 1986), reading comprehension (Clark & Ishida, 2005;Park, 2012), writing skills (Cobb & Horst, 2015;Engber, 1995;Gass & Selinker, 2008;Gonzalez, 2013;Grobe, 1981;Shaw, 1991;Townsend & Kiernan, 2015) and academic English proficiency (Townsend, Filippini, Collins, & Biancarosa, 2012).…”
Section: Academic Vocabularymentioning
confidence: 99%